Catalytically active bovine serum amine oxidase bound to fluorescent and magnetically drivable nanoparticles - Sinigaglia, Giulietta (Dove Medical Press, 2012)
Novel superparamagnetic surface-active maghemite nanoparticles (SAMNs) characterized by a diameter of 10 ± 2 nm were modified with bovine serum amine oxidase, which used rhodamine B isothiocyanate (RITC) adduct as a fluorescent spacer-arm. A fluorescent and magnetically drivable adduct comprised of bovine serum copper-containing amine oxidase (SAMN–RITC–BSAO) that immobilized on the surface of specifically functionalized magnetic nanoparticles was developed. The multifunctional nanomaterial was characterized using transmission electron microscopy, infrared spectroscopy, mass spectrometry, and activity measurements. The results of this study demonstrated that bare magnetic nanoparticles form stable colloidal suspensions in aqueous solutions. The maximum binding capacity of bovine serum amine oxidase was approximately 6.4 mg g(−1) nanoparticles. The immobilization procedure reduced the catalytic activity of the native enzyme to 30% ± 10% and the Michaelis constant was increased by a factor of 2. We suggest that the SAMN–RITC–BSAO complex, characterized by a specific activity of 0.81 IU g(−1,) could be used in the presence of polyamines to create a fluorescent magnetically drivable H(2)O(2) and aldehydes-producing system. Selective tumor cell destruction is suggested as a potential future application of this system.